27. THE SEMI-RIGID URETEROSCOPY LITHOTRIPSY WITH HOLMIUM LASER FOR URETERAL STONES IN ELDER OVER 70 YEARS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the effectiveness and safety of ureteral lithotripsy using a semi-rigid ureteroscope with the Accutech Laser Lithotripter lithotripter in elderly people over 70 years old.Method: Retrospective study was conducted on 200 patients over 70 years old undergoing endoscopic lithotripsy at Thong Nhat Hospital from January 1, 2020 to August 30, 2023. Patients over 70 years were studied on rate factors. stone clearance, complications during and after surgery, factors affecting surgery in elderly people over 70 years old including age, gender, underlying diseases such as hypertension, diabetes, etcResults: Average age 75.67±4.5 years old, 85(42.5%) patients with hypertension, 75(37.5%) patients with diabetes, 34(17%) patients with coronary artery disease, 56(28%) %) patients are using antiplatelet drugs, 12(6%) patients are using oral anticoagulants treatment, 57(27.5%) patients have chronic kidney disease, 56(28%) patients have respiratory diseases, etc. Stone size 10.22±2.76 mm, location: junction 14(7%) patients, upper 1/3 124(62%) patients, middle 1/3 25(12.5%) patients, lower 1/3 37(18.5%) patients, anesthesia method: endotracheal anesthesia 140(70%) patients, spinal anesthesia 60(30%) patients, surgery time 29.45±12.08 minutes, clean rate 94% of stones, number of days in hospital 7.55±1.81 days. Complications during and after surgery occurred in patients: 12 patients could not be removed, 14 patients had urinary tract infection, 2 patients had ureteral perforation, 4 had heavy bleeding during surgery.Conclusion: Endoscopic laser ureteral lithotripsy with a semi-rigid ureteroscope in elderly people over 70 years old is a safe and effective method with a low complication rate and high stone clearance rate.
Keywords: Ureteroscopic lithotripsy; ureteral stones in the elderly